DECADAL CHANGE IN RIVER DYNAMICS AND LAND-USE LAND COVER PATTERN IN KALIGANDAKI RIVER VALLEY FROM 1988-2017 - Suzata Karki (International Association of Lowland Technology, 2021)
Abstract The Kaligandaki basin is a snow-fed river system. It encompasses Trans-Himalayan to the Gangetic plain through Higher Himalayan, and Lesser Himalayan zones and Siwalik. This region is exposed to extensive landslides and flood hazards and are susceptible to massive land use and land cover changes every year. The present study deals with land use land cover (LULC) changes and river dynamics of the Kaligandaki river valley from Jomsom to Kusma between the years 1988-2017 using GIS as a tool. The study further focuses on change in river courses with depositional and erosional areas that further causes fluctuations to the sediment area. Decadal LANDSAT images of 30m resolution were considered for the study over 3 decades divided into five stages 1988, 1995, 2000, 2008, 2017. Radiometric correction for those images were done using QGIS, Supervised Maximum Likelihood (SML) classification into six classes viz., water bodies, forest, shrubland, agriculture and grassland, settlement, sediment and bare land, snow were applied. Analysis shows that the Kaligandaki river is a sinuous river. The bankline shift is highest (84.7109m) from 1995-2000 in the upper part of Jomsom and Lete where the width tends to fluctuate the most due to the wide floodplains and the lowest (0.20836m) from 2000 to 2008 in the lower sections where the river is more narrow. In almost three decades , water bodies in the study area has an overall decrease of 1% (15.76 km²); Forest and shrub land decreased by 5% (80.31 km²); Agriculture and grassland increased by 1% (16.22 km²); Settlement increased by 4% (67.23 km²); Sediment and bare land increased by 2% (29.42 km²) and snow cover decreased by 1% (16.81 km²). Keywords: LULC, Sinuosity, GIS, SML